MADRASAH EFEKTIF Kontribusi Kepemimpinan, Kinerja Guru dan Kompetensi Pengawas terhadap Mutu Pembelajaran di Madrasah Ibtidaiyah Swasta Kota Bandar Lampung - Patimah, Hj. Siti (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2017)
The implications of the low quality of results achieved by the Islamic schools, illustrate the low quality of their teaching and learning process. Head of Madrasah, Supervisors and teachers play a very important role in realizing a quality learning process. Given that the three organizations are one of the keys to the success of the teaching and learning process, improving the performance of the headmaster, supervisors and teachers is a must. In this study there are several factors that are considered to contribute to the quality of learning including leadership, teacher performance and supervisor competence      This research was carried out using quantitative approaches and descriptive survey methods. The population is the Bandar Lampung City MIS teacher spread in 7 Private Madrasas with 132 people. The number of research samples is 56 teachers using the Krecjie Morgan formula, and the selection technique is proportional random sampling. Research data was collected through questionnaires and analyzed using descriptive statistical techniques and regression analysis.      Based on the data analysis, the following findings and conclusions were obtained: first, there was a significant contribution of leadership to the quality of learning in Bandar Lampung's MIS of 16.3% with moderate correlation strength (0.403). Second, there is a significant contribution of teacher performance to learning quality by 21.2%. The strength of the relationship of teacher performance to the quality of learning is moderate (0.460), Third, there is a significant contribution of supervisory competence to the learning quality of 18.3%. with the strength of the medium relationship (0.428).Based on the results of these studies it can be stated that the quality of learning can be improved through: leadership improvement, teacher performance and supervisor competency. Principals as elements of leadership through their policies must provide maximum facilities in order to realize quality learning. Teachers as the spearhead of the learning process must improve their performance and so do the supervisors of education must have adequate competence in carrying out their main tasks and functions as academic supervisors and supervisors of the education unit. Key Words: Kepemimpinan, Kompetensi Pengawas dan Kualias Pembelajaran